Role of education in reducing child labour: a case from rural Bangladesh - Nath, Samir Ranjan; Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
This article examines the hypothesis that formal education of children and their parents plays a major role in reducing child labour. Data are generated from a representative sample survey of 3,809 children aged 10-14 years in 150 villages of Manikganj and Joypurhat districts in Bangladesh. Findings reveal significant inverse relationship between child labour and years ol schooling. Six factors such as age of children, child education, mother's education, father's education, land ownership of household and father's occupation appear to be important determinants of child labour. Probabilities of children to be in the labour force also indicate that years of schooling of the children is the most influential variable to reduce child labour followed by father's and mother's education. It is concluded that child labour may be reduced by enrolling children to school. This should be ensured through motivating the parents for education, making available of schools in rural areas, and creating a joyful environment of learning.